2017
DOI: 10.1007/s11060-017-2619-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating progression-free survival in patients with glioblastoma using routinely collected data

Abstract: Glioblastoma (GBM) represents 80% of all primary malignant brain tumours in adults. Prognosis is poor, and there is a clear correlation between disease progression and deterioration in functional status. In this pilot study we assess whether we can estimate disease progression and progression free survival (PFS) from routinely collected electronic healthcare data. We identified fifty patients with glioblastoma who had chemo-radiotherapy. For each patient we manually collected a reference data set recording dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Therefore, identifying biomarkers which would predict prognosis at an early time point during treatment is crucial. The median PFS is heterogeneous, and frequently ranges from 6 to 8 months [ 27 , 28 ]. In this study, we therefore chose the third quartile (6–9 months after the start of the adjuvant treatment) as a time for measuring microRNAs in serum and serum-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying biomarkers which would predict prognosis at an early time point during treatment is crucial. The median PFS is heterogeneous, and frequently ranges from 6 to 8 months [ 27 , 28 ]. In this study, we therefore chose the third quartile (6–9 months after the start of the adjuvant treatment) as a time for measuring microRNAs in serum and serum-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study used electronic records from 50 patients with GBM to assess OS and PFS in an effort to estimate national OS and PFS using routinely collected data. This study reported that patients treated with chemotherapy and radiotherapy had a median PFS of 7.4 months and median OS at 12.8 months or 68% one-year OS [78]. Therefore, the numbers reported in the GlitIpNi trial are not encouraging.…”
Section: Clinical Experience With Using Icis To Treat Gbmmentioning
confidence: 94%
“…Glioblastoma progresses in almost all patients. At progression a standard of care is unavailable and management varies from best supportive care or re-challenge of temozolomide to additional combination treatments or clinical trial participation [ 1 3 ]. The definition of progressive disease is ambiguous due to unreliable differentiation between treatment-related imaging phenomena and true disease progression.…”
Section: Introductionmentioning
confidence: 99%